Power Electronics Innovations: Improving Efficiency and Sustainability in Energy Systems - Dhameliya, Niravkumar (Asia Pacific Journal of Energy and Environment, 2022)
This study examines how power electronics advancements might alter energy system efficiency and sustainability. The main goals were to study wide bandgap (WBG) semiconductor materials, control algorithms, renewable energy integration, and future trends and problems. Synthesizing current knowledge and trends from peer-reviewed literature, conference papers, and industry reports was done using secondary data. Significant discoveries show that WBG semiconductors like SiC and GaN have superior electrical characteristics, improving power electronic device efficiency and reliability. Model predictive control (MPC) and AI-based control algorithms optimize system performance and handle renewable energy source variability. Modern inverters and converters help integrate renewable energy into the grid, improving energy efficiency and the environment. Policy implications underline the need for supporting regulatory frameworks, research funding, and industry collaboration to reduce cost barriers, ensure interoperability, and optimize power electronics breakthroughs in global energy transitions.